Remote controlled laboratory experiments on the web - Stefanovic, Miladin Z; Matijevic, Milan S; Cvjetkovic, Vladimir (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:238; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:SR; mso-fareast-language:SR;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:70.85pt 56.7pt 70.85pt 85.05pt; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->The purpose of this paper is to present organization and development of web laboratory exercises in Web Laboratory, University of Kragujevac. WebLab provides remote access to real laboratory equipment using contemporary computer and network technology for creating the environment that will enable the remote user to perform the required laboratory exercises and control the laboratory equipment. This paper presents pre-requests, architecture and software realization of web based laboratory. Using feedback from survey we will present framework for web laboratory and web lab experiment in order to incorporate practical work and laboratory exercises in integrated e-learning environment. Realizations of two laboratory experiments developed using different platforms are presented, compared and contrasted. Finally some educational results of usage of web laboratory in industrial engineering education are presented.